Systematic review of lifestyle interventions to limit postpartum weight retention: implications for future opportunities to prevent maternal overweight and obesity following childbirth. Issue 10 (17th June 2013) - van der, P.; Willcox, J.; Hesketh, K. D.; Ball, K.; Wilkinson, S.; Crawford, D.; Campbell, K.
Summary Postpartum weight retention can predict future weight gain and long‐term obesity. Moreover, failure to lose weight gained during pregnancy can lead to increased body mass index for subsequent pregnancies, increasing the risk of adverse maternal and foetal pregnancy outcomes. This systematic review evaluates the effectiveness of lifestyle interventions aimed at reducing postpartum weight retention. Seven electronic databases were searched for intervention studies and trials enrolling women with singleton pregnancies and published in English from January 1990 to October 2012. Studies were included when postpartum weight was a main outcome and when diet and/or exercise and/or weight monitoring were intervention components. No limitations were placed on age, body mass index or parity. Eleven studies were identified as eligible for inclusion in this review, of which 10 were randomized controlled trials. Seven studies were successful in decreasing postpartum weight retention, six of which included both dietary and physical activity components, incorporated via a range of methods and delivered by a variety of health practitioners. Few studies utilized modern technologies as alternatives to traditional face‐to‐face support and cost‐effectiveness was not assessed in any of the studies. These results suggest that postpartum weight loss is achievable, which may form an important component of obesity prevention in mothers; however, the optimal setting, delivery, intervention length and recruitment approach remains unclear.